Nutritional screening and nutritional interventions in patients following gastrointestinal surgery in a general surgical ward: a best practice implementation project. Issue 4 (5th December 2021) - Zhang, Qi; Yu, Zhenghong; Qi, Birong; Ni, Xiaohong; Moola, Sandeep
ABSTRACT: Objectives: The aim of this implementation project was to improve nutritional screening and nutritional interventions for patients scheduled for gastrointestinal surgery in a general surgical ward. Introduction: Malnutrition is common in hospitalized surgical patients and has many adverse outcomes affecting the patients' quality of life. Improving nutritional risk screening and nutritional support could reduce the incidence of malnutrition and its adverse outcomes. Methods: The project used the JBI audit and feedback method to implement evidence into practice. JBI Practical Application of Clinical Evidence System and Getting Research into Practice audit tools were used for promoting change in general surgical wards. Six audit criteria were created based on an evidence summary, including using screening tool, patients' and caregivers' education, nurses' education on nutritional screening and support, preoperative nutrition support and postoperative early food intake. A baseline audit was conducted, followed by nursing information system improvement, education, multidisciplinary meetings targeted at clinicians and two cycles of follow-up audits. Results: Results from the baseline and follow-up audits showed improvement for all the criteria. Compliance for criteria 1–3 increased from 0 to 100%, and that for criterion 4 increased from 32 to 100%. These four criteria sustained 100% in follow-up cycle 2. Compliance for criterion 5 increased from 8 to 50% in follow-up cycle 1 audit, but decreased to 0% in follow-up cycle 2 audit, and similarly for criterion 6, compliance increased from 45 to 56% in follow-up cycle 1 audit, but decreased to 48% in follow-up cycle 2 audit. Conclusion: The objectives related to nutritional risk screening, nurse knowledge, patients and families were successfully realized and sustained positive results. This project demonstrated that a nursing information system and long-term patient education are essential strategies to achieve and sustain positive results. The objectives related to preoperative nutritional support and postoperative early enteral food intake were challenges and represented barriers. In future, a multiple-pronged strategy will be implemented to achieve overall success and change according to best practice.